REDESIGNING THE UI/UX WEBSITE FOR THE INDUSTRIAL ENGINEERING DEPARTMENT AT MULAWARMAN UNIVERSITY USING DESIGN THINKING METHOD - Hadi, Amirul; Sukmono, Yudi; Harjanto, Arif; Suprihanto, Didit (Jurnal Teknik Informatika (Jutif), 2024)
The industrial engineering department website of Mulawarman University faces challenges in disseminating academic information due to inadequate maintenance. This research utilizes the design thinking method to enhance the website's user interface and user experience (UI/UX) and evaluate its usability against the current version. The decision to use design thinking is grounded in its established effectiveness in improving website UI/UX. The study involves empathizing, defining, ideating, prototyping, and testing phases. User needs and concerns were identified through interviews, observations, and tools such as affinity diagrams, user personas, and user journey maps. Creative concepts were developed and organized using the priority matrix, sitemap, and user flow. Wireframes and mockups facilitated pre-construction design visualization. The redesigned UI/UX prototype resulted in a significantly improved user experience, as evidenced by the results of the user experience questionnaire and system usability scale. The initial UEQ scores indicated low usability, with attractiveness at 0.85, perspicuity at 1.01, efficiency at 0.71, dependability at 0.76, stimulation at 0.41, and novelty at -0.18. Following the redesign, scores notably increased, attractiveness at 2.06, perspicuity at 1.89, efficiency at 1.94, dependability at 1.79, stimulation at 2.05, and novelty at 1.64. SUS testing revealed an average rise to 76 from 63 points, indicating enhanced user satisfaction, acceptance, and descriptive ratings. The website's grade improved from C to B after the redesign. In conclusion, the UI/UX redesign successfully enhanced website usability and user experience.